A Brief Review of Scanning Electron Microscopy With Energy-Dispersive X-ray Use in Forensic Medicine. (December 2020) - Gentile, Guendalina; Andreola, Salvatore; Bailo, Paolo; Battistini, Alessio; Boracchi, Michele; Tambuzzi, Stefano; Zoja, Riccardo
Abstract : Abstract: Scanning electron microscopy with energy-dispersive x-ray (SEM/EDX) analysis is an investigation whose potential has become increasingly important in the field of forensic research and diagnosis. We present the procedure to perform a well–carried-out SEM/EDX analysis on corpses affected by different types of injuries, such as blunt force trauma, ligature strangulation, electrocution, sharp force trauma, gunshot wounds, and intoxication. After the areas of forensic interest have been macroscopically identified, the sampling can be performed in 2 different ways: apposition of the double-sided graphite tape on the damaged area or performing the excision of a biological sample. In both cases, a proper negative control sample is required. In all cases, SEM/EDX analysis can detect exogenous microtraces consistent with the types of injuries involved. In blunt force trauma, microparticles of different nature deriving from the contact of the blunt instrument with the victim may be observed; in sharp force trauma, metal microtraces (Fe, Cr, Al, Ti) can be identified. In ligature strangulation, exogenous microtraces may be found in the cutaneous furrow. In electrocution, it allows to identify the pathognomonic metal pattern (Cu, Zn, Fe) of the "electric mark." In gunshot wounds, the main applications regards the detection of metal particles (Pb, Ba, Sb) of gunshot residues. Finally, in the analysis of intoxicants, it may identify traces of toxic substances. Thus, the authors conclude that SEM/EDX analysis can provide essential information to assist in the medicolegal investigation of death.